Modeling of the axial distributions of volatile species in a circulating fluidized bed boiler. (6th April 2021) - Ke, Xiwei; Engblom, Markus; Zhang, Man; da Silva, Paulo S.P.; Hupa, Leena; Lyu, Junfu; Yang, Hairui; Wei, Guohua
Graphical abstract: There are two peaks in the axial distribution of total released volatiles: coal inlet area and bottom dense bed, which is mainly attributed to the wide size range of feeding fuel. Highlights: A model is developed aiming at the axial distributions of volatiles in a CFB boiler. There are two peaks in the axial distribution of total volatiles. Quantitatively the release profiles of individual volatile species are different. More volatile-N will be released above dense bed if the feeding fuel size decreases. The share of volatile-N in dense bed only changes a little if temperature increases. Abstract: The proper understanding and description of the spatial distributions of volatile species is important to the circulating fluidized bed (CFB) reactor design and modeling. Aiming at this issue, a mathematical model has been developed in the present work, which constitutes of two main modules that are validated by experiments, one-dimensional fluid dynamic model and single fuel particle devolatilization model. The simulation of a 135 MWe CFB boiler was conducted. Results show that all volatile species exhibit in general a vertical release profile of bimodal shape (coal inlet area and bottom dense bed) while with quantitative differences, which is mainly attributed to the wide size range of feeding fuel. Compared to the influence of bed temperature, the effect of feeding coal size on the volatile nitrogen release is more obvious. This model can be applied as the devolatilization sub-model for the integral combustion simulation of a CFB boiler.